PERENCANAAN EMBUNG SOMOSARI DI JEPARA - Hesti Astria Utami; Galang Sri Nalendra; Sriyana Sriyana; Priyo Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Somosari Village and its surrounding area in Jepara District is currently having a decline in its water resources. This condition is indicated by the drop of ground water level, the drought among its river and the reduction of water availability through out its irrigation. On the counting, this condition is contrasted by the flood during the rainy season. An alternative solution to the conditions is to build small dam in Somosari Village. The small dam is function as water reservoir, flood control, and conservation. The final project was based on some complementing methods. The first method is hydrological analysis which included storage capacity analysis using simulation. The other hydrological analysis are analysis of flood discharge using Weduwen Methods, discharge mainstay analysis using Basic Year Methods, water demand analysis and water balance analysis. The last phase is small dam construction planning. The result suggest that Somosari Small Dam will have 100752.736 m3 storage capacity, handle the flood debit of 426,279 m3/sec with cycle period of 100 years. The small dam is planned to be build as high as 18 m with the base elevation degree +274.48, and effective width of 22.127 m. The small dam constructed using K 300 concret and fill soil with estimated cost of Rp 20,814,178,800.00 (twenty billion eight hundred fourteen million one hundred seventy eight thousand and eight hundred Rupiah).